2005
DOI: 10.1074/jbc.m411465200
|View full text |Cite
|
Sign up to set email alerts
|

A Surface Phospholipase Is Involved in the Migration of Plasmodium Sporozoites through Cells

Abstract: Plasmodium sporozoites, injected by mosquitoes into the skin of the host, traverse cells during their migration to hepatocytes where they continue their life cycle. The mechanisms used by the parasite to rupture the plasma membrane of the host cells are not known. Here we report the presence of a phospholipase on the surface of Plasmodium berghei sporozoites (P. berghei phospholipase; Pb PL) and demonstrate that it is involved in the establishment of a malaria infection in vivo. Pb PL is highly conserved among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 32 publications
2
98
0
2
Order By: Relevance
“…It is likely that these proteins are also required for sporozoite exit from the dermis and in the case of the SPECT 1 knockout this has been recently directly demonstrated by intravital microscopy [Amino and Menard, unpublished data]. The fourth protein, a phospholipase, has a carboxy-terminal domain with significant similarity to mammalian LCATs (lecithin:cholesterol acyl transferases) and when expressed as a recombinant protein has lipase and membrane lytic activity [30]. Mutant sporozoites in which PL is deleted or its catalytic site altered, are impaired in reaching the liver when injected intradermally but have normal infectivity when injected intravenously.…”
Section: Migration In Apicomplexan Parasitesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that these proteins are also required for sporozoite exit from the dermis and in the case of the SPECT 1 knockout this has been recently directly demonstrated by intravital microscopy [Amino and Menard, unpublished data]. The fourth protein, a phospholipase, has a carboxy-terminal domain with significant similarity to mammalian LCATs (lecithin:cholesterol acyl transferases) and when expressed as a recombinant protein has lipase and membrane lytic activity [30]. Mutant sporozoites in which PL is deleted or its catalytic site altered, are impaired in reaching the liver when injected intradermally but have normal infectivity when injected intravenously.…”
Section: Migration In Apicomplexan Parasitesmentioning
confidence: 99%
“…Although we are still far from a molecular understanding of this process, four proteins involved in cell traversal recently have been identified. Three of these, SPECT 1 (sporozoite microneme protein essential for cell traversal) and SPECT 2 (also called perforin-like protein 1; PLP1) and CelTOS (cell traversal protein for ookinetes and sporozoites) were identified using EST databases [25][26][27][28] while the fourth, a phospholipase (PL) was found using an RNA subtraction screen that identified genes up-regulated in salivary gland sporozoites [29,30]. Expression of SPECT 1, SPECT 2 and PL are specific to salivary gland sporozoites whereas CelTOS is expressed by both ookinetes and salivary gland sporozoites.…”
Section: Migration In Apicomplexan Parasitesmentioning
confidence: 99%
“…In particular, the product of phosphatidylcholine lysis, lysophosphatidylcholine, possesses a strong membrane lytic activity (40,41). To investigate the potential effect of TgLCAT on cell membranes, we generated a recombinant form of TgLCAT (rTgLCAT) using the baculovirus expression system (42), as we previously exploited to engineer recombinant Plasmodium LCAT (43). The culture medium of SF21 cells infected with baculoviruses containing the Toxoplasma lcat gene was analyzed by Western blot using anti-TgLCAT antibodies (Fig.…”
Section: T Gondii Has a Unique Gene Homologue To Lecithinmentioning
confidence: 99%
“…The orthologue of this enzyme in P. berghei, PbPL, was shown to support PVM rupture during parasite egress from the hepatocyte as discussed below (Burda et al, 2015). The PLA and membrane lytic activities of PbPL were demonstrated (Bhanot et al, 2005), potential acyltransferase activities have yet to be shown. Furthermore, two enzymes, which belong to the phosphodiestercleaving group, are encoded in the genome of P. falciparum.…”
Section: Phospholipases Of Plasmodial Parasitesmentioning
confidence: 98%
“…a putative lecithin:cholesterol acyltransferase (LCAT; PFD37_0629300), which was demonstrated to be involved in membrane dynamics during hepatocyte invasion and egress by P. berghei parasites. This phospholipase, termed PbPL, exhibits membrane lytic activity in vitro and following hepatocyte infection, PbPL localizes to the PVM (Bhanot et al, 2005;Burda et al, 2015). Upon genetic knock-out, PbPL-deficient sporozoites lose their infectivity and their ability to cross epithelial cell layers.…”
Section: The Role Of Plasmodial Phospholipases During Life-cycle Progmentioning
confidence: 99%